Structure of Fisher (Pekania pennanti) Habitat in a Managed Forest in an Interior Northern California Coast Range. Issue 3 (4th December 2014) - Niblett, Matthew R.; Sweeney, Stuart H.; Church, Richard L.; Barber, Klaus H.
Abstract : Forest management planning across the Sierra Nevada and Northern California includes several focal wildlife species, one of which is the fisher, recently reclassified as Pekania pennanti (Sato et al. 2012 ) from Martes pennanti . This article presents an analysis of fisher habitat associated with privately owned forestland in Northern California. We take advantage of a high-resolution inventory database to show selective use of female fishers within this landscape. This landscape can be thought of as a matrix containing scattered mature stands of conifers and hardwoods (age >100 years) within a landscape of younger mixed conifer stands and numerous openings (24% of the area). Although stand and forest averages for habitat elements appear to score poorly using a widely used metric, we demonstrate through a new form of spatial sampling using a Kolmogorov-Smirnov (K-S) statistical test, which we call k -max, selective habitat use by female fishers at a relatively fine scale. This approach is novel in terms of generating population-level inferential results that are sensitive to smaller scale selection behavior, demonstrating that existing large structures, even though limited in areal extent, are critical elements in female fisher habitat.